A route to the dispersion of ultrafine cobalt particles on zeolite Na-X through salt occlusion and reduction - Hussain, I; Gameson, I; Anderson, P; Slaski, M; Edwards, P; Dyer, A (1996)
Ultrafine magnetic cobalt particles, encapsulated within a zeolitic host, have been prepared via the seldom-used method of salt occlusion followed by reduction to the metallic state. Powder X-ray diffraction and electron microscopy clearly showed the formation of 150-250 Å cobalt particles which were too large to be contained in the supercage of the zeolite. An increase in cobalt content increases the number of these cobalt particles, but not their size. We thus propose that these particles are encapsulated within locally distorted areas of the zeolite structure. This work demonstrates the clear potential of zeolites as templates or host matrices for the synthesis of ultrafine metal particles.